PERAN KEPALA DESA DALAM PENGELOLAAN DANA DESA DI KECAMATAN ESSANG SELATAN KABUPATEN KEPULAUAN TALAUD - MADEA, YOLANDA; Laloma, Alden; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
abstract : The phenomenon in the management of village funds, the Village Head as the holder of the power of financialmanagement and village assets, in determining the budget of village income and expenditure does not involve the componentsof society other than that the obligation to submit reports on the implementation of APBDes to the community is notimplemented. Based on the background of the problem, the purpose of this research is to know / explain the role of villagehead in managing the village fund in South Essang Subdistrict The type of research used in this study is qualitative research.The focus of this research is the role of village head in the management of village fund in South Essang sub-district.Reviewed on budget planning, implementation, and evaluation. Determination of informants is based on the criteriaaccording to the research objectives. The result of the research shows that the Village Fund Program Planning in SouthEssang Subdistrict has not gradually implemented the concept of village community participation development which isproven by participative, responsive, transparency principle, in order to realize every priority program of society needs.Villages that are held through Musrembangdes, the implementation of the Village Fund program, in the physicaldevelopment, community empowerment has been running in accordance with the planning in musyawarah kan, but theproblem is the lack of supervision by the village government to the people who cheat so that inhibition of village fundmanagement in the field of development and Empowerment. Evaluation for village funds in 2016 already underway but, insuccessful development can not be separated from obstacles in its workKeywords: Village Head, Village Fund Management